(untitled) (Global Journal of Medical Research, 2014)
Generally, in fasting state, gluconeogenesis accounts for about 30% of overall hepatic glucose output, the increase in type 2 diabetic subjects may be much more than this level. There is a close relationship between glucose metabolism and amino acid metabolism which is established through transamination reactions. The key amino acid -keto acid pairs involved in transamination reactions are glutamateα ketoglutarate, aspartate -oxaloacetate and pyruvate -alanine. A study was undertaken to assess the plasma levels of total amino acids, glutamate and alanine in type 2 diabetic subjects. A blood sample (5ml) with heparin as an anticoagulant was collected in the fasting state, from each of the selected normal as well as diabetic subjects. The separated plasma samples were employed for the estimation of total amino acid nitrogen levels, as well as for the estimation of plasma alanineand glutamate levels. The results indicate a significant rise in the plasma levels of total amino acids, alanine & glutamate in type-2 diabetic subjects as well as a significant increase in plasma alanine levels in diabetics of 30-40 yrs age as compared to diabetics of 41-60yrs of age. These findings suggest an increased availability of glucogenic amino acid precursors for glucose formation may be due to lack of proteolytic suppression of insulin.